The DSK-SFC stock-flow consistent agent-based integrated assessment model - Severin Reissl; Luca E. Fierro; Francesco Lamperti; Andrea Roventini (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2024)
We present an updated, stock-flow consistent version of the 'Dystopian Schumpeter meeting Keynes' agent-based integrated assessment model. By embedding the model in a fully specified accounting system, all balance sheet items and financial flows can be explicitly and consistently tracked throughout a simulation. This allows for an improved analysis of climate change and climate policy scenarios in terms of their systemic implications for agent and sector-level balance sheet dynamics and financial stability. We provide an extensive description of the updated model, representing the most detailed outline of a model from the well-established 'Keynes + Schumpeter' family available to date. Following a discussion of calibration and validation, we present a range of example scenarios.
Keywords: E70; C63; Q50; Q54; 330; Climate change; Agent-based models; Integrated assessment